ANALYSIS OF CARBON RESERVES IN THE MANGROVE FOREST ECOSYSTEM OF KUALA INDRAGIRI RIAU PROVINCE - Massugito '; Syahrul Nedi; Bintal Amin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The study was conducted in February-March 2015 on mangrove forest ecosystems in the Coastal Zone of Kuala Indragiri Riau Province. The aim of research was to analyze the content of carbon in mangrove forest ecosystems as well as the ability to store carbon in the forest area. The survey method was applied in this study and carbon analysis was carried out in the Marine Chemistry Laboratory of Faculty of Fisheries and Marine Science of University of Riau. The study showed that the potential mangrove biomass was directly proportional to mangrove carbon stocks. The average yield of biomass and carbon stocks of soil organic carbon reserves amounted to 258.03 tons/ha and 1476.40 tons/ha, while the average yield of total carbon stocks was 1734.43 tons/ha.Keyword: Mangrove, Carbon, Biomass, Organic Soil, Kuala Indragiri.